The Ismália’s Tower Amidst the Gaps of Time: An Occupation of the Ruins of the Church of Nossa Senhora de Belém - Damiani, Sarah Rodrigues; Sanmartin, Stela Maris (Revista do Colóquio, 2026)
This visual essay presents the photo-performance titled “Ismália’s Tower Amidst the Gaps of Time.” The work juxtaposes symbolic elements from the poem *Ismália* (Guimarães, 1963) with the crumbling ruins of the Church of Nossa Senhora de Belém in Viana, Espírito Santo. The occupation of the ruins emerges as a potential path for fostering new imaginaries, inviting the audience to perceive the metaphors and analogies established through this symbolic juxtaposition.